The failure process of mortars during sulfate attack - Liu, Kaiwei (Array, 2019)
External sulfate attacks on concrete structures may cause serious damage and it has attracted a wide range of attention from numerous researchers over the past decades. However, many studies have been concentrated on the sample which has been already destroyed. This paper investigated the entire deterioration process of mortars that were immersed in Na2SO4 solution containing 3 gSO4 2-/L and 33.8g SO4 2-/l at 20 o C up to 600 days. The study on time-varying regularity of expansion, cracks, compressive strength and mineral phases was investigated. Back scattered electron image was used to further examine the evolution of microstructures of the mortars during the attack process. The results showed that damage process of mortars can be described as induction stage, surface damage, bulk damage and then completely damage stage. Fine ettringites that were formed in restricted spaces, approximately 2-5 μm, result in surface damage. At the bulk damage stage, cracking was the main characteristic of mortar which leads to obvious expansion. In this stage, some large ettringite crystals (>20μm) were just deposited in the formed cracks. At the later stage, gypsum can be easily formed at interfacial transition zones as the consumption of calcium hydroxide, which mainly contributed to completely strength failure rather than expansion.